2022
DOI: 10.3389/fimmu.2022.876339
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Manufacturing Procedures on CAR T Cell Functionality

Abstract: The field of chimeric antigen receptor (CAR) modified T cell therapy has rapidly expanded in the past few decades. As of today, there are six CAR T cell products that have been approved by the FDA: KYMRIAH (tisagenlecleucel, CD19 CAR T cells), YESCARTA (axicabtagene ciloleucel, CD19 CAR T cells), TECARTUS (brexucabtagene autoleucel, CD19 CAR T cells), BREYANZI (lisocabtagene maraleucel, CD19 CAR T cells), ABECMA (idecabtagene vicleucel, BCMA CAR T cells) and CARVYKTI (ciltacabtagene autoleucel, BCMA CAR T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 100 publications
1
63
0
Order By: Relevance
“…Cai et al reported the rates of GIAEs were 13% and 10% following tisagenlecleucel and axicel infusion, respectively. significantly more reports of tisagenlecleucel and axi-cel compared to liso-cel and KTE-X19 mainly due to earlier approval time by FDA, which were 2017 and 2021 for tisagenlecleucel and axi-cel ( 8), and liso-cel and KTE-X19 (26), respectively. Overall, males accounted for a larger portion compared with females in all the reports of CAR-T-related GIAEs (57.38% vs. 37.94%).…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al reported the rates of GIAEs were 13% and 10% following tisagenlecleucel and axicel infusion, respectively. significantly more reports of tisagenlecleucel and axi-cel compared to liso-cel and KTE-X19 mainly due to earlier approval time by FDA, which were 2017 and 2021 for tisagenlecleucel and axi-cel ( 8), and liso-cel and KTE-X19 (26), respectively. Overall, males accounted for a larger portion compared with females in all the reports of CAR-T-related GIAEs (57.38% vs. 37.94%).…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al. summarized that co-culturing of T cells with some pharmacological inhibitors (e.g., the IKT inhibitor ibrutinib, BET inhibitor JQ-1) can specifically suppress T cell exhaustion ( 58 ). All of these studies suggested that T cells modifications and cytokines/pharmacal supplementation may significantly improve the efficacy of the final infusion product.…”
Section: Limitation and Recent Advances In Car T Cell Therapies For S...mentioning
confidence: 99%
“…CAR T cells have been shown to have remarkable activity in several hematologic malignancies (91). There are four anti-CD19 CAR T products currently approved for use in B cell acute lymphoblastic leukemia (brexucabtagene autoleucel and tisagenelcleucel) and non-Hodgkin B cell lymphomas (axicabtagene ciloleucel and lisocabtagene maraleucel) (92). The first CAR T product for relapsed MM, idecabtagene vicleucel (idecel), was approved in 2021 for patients who have received 4 or more prior lines including an IMiD, a PI, and a CD38-directed MoAb.…”
Section: Car T Cellsmentioning
confidence: 99%